Ephemera Collection,
Collection of brochures, promotional materials and reports primarily related to the development of Spokane and the Inland Northwest. Some materials are related to the State of Washington or the Pacific Northwest. Some research items were also collected due to their scarcity. This is an artificial collection of printed materials collected by the Spokane Public Library.